B-type natriuretic peptide plasma level in 5-year breast cancer survivors after radiotherapy. (1st February 2019) - Portaluri, Maurizio; Petruzzelli, Maria Fonte; Tramacere, Francesco; Andreassi, Maria Grazia
Abstract: Background: Left-sided breast cancer patients treated with radiotherapy (RT) are at risk for late radiation-induced cardiovascular complications. Aim: The aim of this study was to investigate the BNP plasma levels in long-term breast cancer survivors who received only RT as well to assess whether cardiac dose was associated with BNP values. Methods: Plasma samples for BNP measurement were repeated in 29 patients (63 ± 11 years) who were alive at 5 years after radiotherapy, free of heart disease and available to provide new blood sample. All patients had BNP measurements at baseline. The ΔBNP was measured to analyze the role of marker variations. No patients received chemotherapy. Results: The mean cardiac and ventricle dose were 2.1 ± 1.0 (range 0.02–4.5) Gy and 3.0 ± 1.7 (range 0.02–7.6), respectively. Median value of BNP was 47 pg/mL (interquartile ranges, 26–58.2 pg/mL) at baseline, and 34 pg/mL (interquartile ranges, 17.5–54 pg/mL) at 5 years after radiotherapy. There was no significantly different between two measurements (p = ns). Fifteen (52%) reported an improvement in BNP levels, 1 (3%) no changes and 13 (45%) reported a worsening. There was no correlation between ΔBNP and age (p = ns). When patients were stratified according to the median value of dose–volume data, ΔBNP was significantly higher in patients with increased cardiac D mean ( p = .02) and left ventricle D mean ( p = .009). Conclusion: At 5 years after radiotherapy, median plasma BNP levels remained within the normal range, but the delta-BNP levels are directly related to the heart and ventricular dose received.